Human metapneumovirus found in slinical materials of children with respiratory tract diseases - Logar, Katarina (Zdravniški vestnik, 2006)
Background Human metapneumovirus (hMPV) was first recognized in the Netherlands in 2001. Since then it has been documented all over the world as acause of human respiratory infections in all age groups. The objective of this study was to introduce and optimize an assay for detecting hMPV in clinical material of our patients. To date, there has not been a report that describes the detection of this virus in Slovenia. Methods A total of 58 specimens, randomly collected during 2003/2004 from the patients =< 19 years old with respiratory disease and 20 specimens collected in 1997 were tested for hMPV. Extraction of RNA from frozen specimens and subsequent single-step reverse transcription polymerase chain reaction (RT-PCR) were performed. Humanmetapneumovirus amplicons were determined by electrophoresis in a 2% (w/v) agarose gel. Results Human metapneumovirus was detected in 13/58 (22%) specimens; 10/40 (25%) specimens were, from the upper and 3/18 (17%) from the lower respiratory tract. The mean age of infected patients was 3.2 2.2 years. Out of 13 of the hMPV-positive specimens, 9 were positive also for another respiratory virus. Two of 20 (10%) archival specimens were hMPV-positive. Conclusions This study is the first report about hMPV in Slovenia. Human metapneumovirus was detected as the second most frequent virusafter RSV in children < 3 years of age. The virus was not found in the specimens from the children younger than 2 months. Based on the hMPV-positive results in archival clinical material, it is suggested that hMPV had circulated in Slovenia before the time it was discovered.
Keywords: Age Factors; Child; Diagnosis; diagnostika; dihala; Dihala, infekcije; infekcije; Isolation And Purification; metapnevmovirus; Microbiology; otroci; Otrok; Pneumovirus; Pnevmovirus; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Respiratory Tract Infections; Starostni faktorji; Vero celice; Vero Cells; virus; virusi